Precise Evaluation of Neutron Asymmetry by Thermodynamical Bag Model - Kolangi Kannan2, K. Ganesamurthy1 and S. (Recent Research in Science and Technology, 2011)
Neutron spin asymmetry and the polarized structure functions is precisely evaluated in the kinematic region 0.1< x < 0.9 and by Thermodynamical Bag Model (TBM). The results for and at x=0.33 are consistent with improved precision. The evaluated values of neutron asymmetry are consistent with HERMES data showing a zero crossing around x=0.47, and the value at x=0.60 is significantly positive. The result agrees with constituent quark model predictions at high x, but disagrees with that from leading-order perturbative QCD (pQCD) assuming helicity conservation.